Comparative efficiency of laboratory diagnostic methods of dog toxocarosis - Pohorelova, H. (Scientific Progress & Innovations, 2024)
The causative agents of toxocarosis are cosmopolitan nematode parasites that infect a wide range of domestic and wild animals through several routes of transmission, producing tissue-localized larvae and persistent eggs that can survive in the external environment. Despite the growing awareness of their zoonotic potential and importance for health care, the issue of using highly effective methods of lifelong diagnostics that are easy to use, inexpensive and have high diagnostic efficiency remains relevant. The aim of the work was to compare the effectiveness of the well-known and the proposed method in the diagnosis of toxocarosis in dogs. The proposed method relates to the field of veterinary medicine, namely veterinary parasitology, to methods of coproscopy, in particular, methods of detecting eggs of Toxocara canis nematodes parasitizing dogs. In laboratory conditions, well-known methods of coproovoscopy (Fulleborn’s, Kotelnikov-Khrenov’s, method of coproovoscopy for trichurosis of sheep) and the proposed method for laboratory diagnosis of toxocarosis in dogs were compared. When using the Fulleborn’s method, 80 % of positive samples were detected, and when using the Kotelnikov-Khrenov’s method, the method of coproovoscopy for sheep trichurosis, and the proposed method, 100 % of positive samples were detected. Indicators of the intensity of toxocarous infestation in dogs when applying the Fulleborn’s method averaged 61.7 eggs/g, Kotelnikov-Khrenov’s – 88.3 eggs/g, the method of coproovoscopy for sheep trichurosis – 88.8 eggs/g, the proposed method – 102.1 eggs/g. It was proved that the proposed method of laboratory diagnosis of toxocarosis in dogs was more effective compared to the method of Fulleborn by 39.6 %, Kotelnikov-Khrenov – by 13.5 %, and the method of coproovoscopy for trichurosis of sheep – by 13.0 %. When applying the proposed method, high coagulation properties of the improved floatant were established relative to undigested feed residues. The obtained results of experimental studies allow us to recommend the proposed method for effective laboratory diagnosis of toxocarosis in dogs.